Student learning processes in classroom and remote laboratory settings - Treagust, David; Carter, Damien; Lindsay, Euan; Zadnik, Marjan; Mocerino, Mauro; Lucey, Anthony (2016)
Existing literature of both classroom and remote laboratories has focused more on learning outcomes and less on learning processes. This project aims to examine the mechanisms through which students learn in classroom and remote laboratory settings and answer key questions such as: With whom and with what do students interact, and what is the purpose of these interactions?, How do the patterns of these interactions correlate with students’ learning and assessment outcomes?, and Which of these interactions must be preserved in a shift to the remote access mode? These questions are answered by observing, recording and analysing students in physical laboratory classes and by using this analysis to guide the development of the next generation of remote laboratory interfaces. The presentation will provide a summary of the background literature and update of progress on the research project.